Superconducting order parameter of Sr2RuO4: A microscopic perspective - Ramires, Aline [UNESP]; Sigrist, Manfred (Amer Physical Soc, 2019)
The character of the superconducting phase of Sr2RuO4 is the topic of a longstanding discussion. The classification of the symmetry allowed order parameters has relied on the tetragonal symmetry of the lattice and on cylindrical Fermi surfaces, usually taken to be featureless, not including the nontrivial symmetry aspects related to their orbital content. Here we show how the careful account of the orbital degree of freedom and a three-dimensional description lead to a much richer classification of order parameters. We analyze the stability and degeneracy of these new order parameters from the perspective of the concept of superconducting fitness and propose new order parameter candidates which can systematically account for the observed phenomenology in this material.